Competency Evaluation With the Supp ort of a Learning Management System - Cardona Torres, Sergio Augusto; Jaramillo Valbuena, Sonia; Navarro Rangel, Yadira (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents the results of a correlational descriptive research for two purposes defined, on the one hand, analyze student opinion regarding the contribution of the methodology of evaluation of training projects for process skills training are presented, on the other side, make a comparative analysis between the results of the evaluation of evidence by students and teacher assessment. The experiment was conducted with students in a course of formal logic undergraduate program Systems Engineering and Computer Science, Universidad del Quindío, Colombia. To support the skills assessment process, it developed a new technology component that is incorporated as a block to learning management system Moodle. Work results support the conclusion that students consider that active participation in the evaluation process contributes to the development of the skills of the course. Regarding the results of the evaluation of evidence, it was identified that there is statistically significant between the evaluation by students and teacher assessment difference.